Juozo Pikčilingio lingvistinės lietuvių kalbos stilistikos teoriniai pagrindai - Knabikaitė, Vaida (Kalbotyra, 2002)
The noted Lithuanian linguist Juozas Pikčilingis, who is regarded as the initiator of Lithuanian linguistic stylistics, began his research into stylistics in the beginning of the fifties of the 20th century. His aim was to create the descriptive theory of Lithuanian linguostylistics. Juozas Pikčilingis presented theoretical substantiation of linguostylistics according to: (1) the practice of normative stylistics, traces of which were seen already in 16–19th century Lithuanian literature, (2) the principles used by Jonas Jablonskis to establish the norms of Standard Lithuanian, (3) views of Charles Bally, the initiator of the general linguostylistics, (4) the theory of the Prague school about the functional stylistics in the thirties of the 20th century, (5) the works of Russian scientists in the fifties and the sixties. Professor Pikčilingis’ theoretical definition of linguostylistics makes it possible to incorporate some issues like style culture and the sense of style into the object of linguostylistics. Besides, the main goals of linguostylistics – the description of the system of Lithuanian stylistic means, its stylistic abilities and to describe the functional styles of Lithuanian language was concorded with the question of good style. In his research into the system of stylistic possibilities of language Professor Pikčilingis was encouraged by the practical studies of German scientists and by the works of Jonas Jablonskis, Juozas Balčikonis, also by the tradition of Motiejus Gustaitis’ “Stylistics” (1923. Juozas Pikčilingis was able to systematise all these different opinions and create Lithuanian linguistic stylistics.